Green supply chain management framework for supplier selection: an integrated multi-criteria decision-making approach. Issue 3 (3rd July 2022) - Ghosh, Sudipta; Mandal, Madhab Chandra; Ray, Amitava
ABSTRACT: This research aims to propose a green supply chain management framework to evaluate supplier organizations. A real-world supplier selection problem is considered, in which three India-based supplier organizations are selected from three different industrial segments, namely, Organization A (service organization), Organization B (manufacturing organization), and Organization C (process organization). Six important criteria are identified from the literature, which encompass both the environmental, economic, and operational aspects of the sustainability. Data is collected through developing a questionnaire, establishing a committee of experts from the strategic, tactical, and operational levels, and carrying out surveys. An integrated multi-criteria decision-making approach is proposed in which the entropy method determines criteria weights and complex proportional assessment, technique for order of preference by similarity to ideal solution, and grey relational analysis rank the supplier organizations separately. Results show that the manufacturing organization is the benchmark organization and its strategies can guide other organizations to enhance their performance. Results also reveal that 'Total energy consumption', 'Total scrap material generation', and 'Renewable energy utilization' are the influential parameters that should predominantly be considered for green supplier selection. This research may assist policymakers to build appropriate sourcing strategies for overall sustainable development.